Views and Counterviews (Dialog, 2002)
Jim Childs, The ELCA and Sexuality: Update Number 1, p.245 Steve Lenius, Regarding “Bishops, Genes, and Sex” by Jarmo Tarkki in Dialog 40:3 (Fall 2001): 233–235., p.246